Promoter architecture and the evolvability of gene expression - Tirosh, Itay (BioMed Central, 2009)
Evolutionary changes in gene expression are a main driver of phenotypic evolution. In yeast, genes that have rapidly diverged in expression are associated with particular promoter features, including the presence of a TATA box, a nucleosome-covered promoter and unstable tracts of tandem repeats. Here, we discuss how these promoter properties may confer an inherent capacity for flexibility of expression.